Comparison of Proliferating Cell Nuclear Antigen Expression in Odontogenic Keratocyst and Ameloblastoma: An Immunohistochemical Study - Hiroshi Takahashi; Shuichi Fujita; Shigeru Yamabe; Takeshi Moriishi; Haruo Okabe; Yoshifumi Tajima; Akio Mizuno (Analytical Cellular Pathology)
Proliferating cell nuclear antigen (PCNA) is a nuclear protein synthesized in the late G1 and S phase of the cell cycle, and immunohistochemical detection of the protein represents a useful marker for the proliferating fraction of cells in tissue specimens. PCNA expression was studied in odontogenic keratocysts (n = 15) and ameloblastomas (n = 46) using an avidin–biotin–peroxidase complex method on routinely processed paraffin sections. The percentage of PCNA-positive cells determined by point counting was significantly lower in the ameloblastomas (mean 9.4%, standard deviation (SD) 11.0) than in odontogenic keratocysts (mean 29.9%, SD 24.0). In ameloblastomas, the mean percentage of PCNA-positive cells was lowest in the acanthomatous pattern and highest in plexiform pattern. The mean percentage of PCNA-positive cells in plexiform pattern was non-significantly higher than that in follicular pattern. The mean percentage of PCNA-positive cells in plexiform and follicular patterns was significantly higher than that in cyctic and acanthomatous patterns. The frequency of PCNA-positive cells was significantly higher in the peripheral cells of follicular and plexiform patterns than in the central cells of both patterns (p < 0.01). Therefore, peripheral cells were regarded as reserve cell of central cells. The mean percentage of PCNA-positive cells in the epithelial lining of odontogenic keratocyst was not significantly different from those in the peripheral cells of follicular and plexiform patterns of ameloblastoma. In contrast, the odontogenic keratocyst exhibited a mean percentage of PCNA-positive cells which was statistically higher than that in other histological elements of ameloblastomas. The present study suggests that odontogenic keratocyst is regarded as benign odontogenic tumour.